Anne of Green Gables (1908) e o romance de formação feminino, uma leitura política - Augusto, Pamela Giovana (2024)
This master’s thesis studies with the book Anne of Green Gables (1908), written by Canadian author Lucy Maud Montgomery. The aim of this research is to present a political reading of the novel, as proposed by critic Fredric Jameson (1992). We are going to analyze the formation process of a female protagonist. Showing how she reconciles the oppositions of a woman's social role and her personal dreams in the equally developing Canadian society. To do so, it will be necessary to historicize the book and understand it within the Female Bildungsroman literary genre - a novel of female development. This genre was born as a masculine expression and scope. Later it was occupied by women. Our specific aim is to show how society is built in an environment of English patriarchal heritage, creating differences and oppressing its citizens and how this order is challenged by new ideas for the role of women. To achieve this goal, we will follow the assumptions of Anglo-American feminist criticism and Jameson's contemporary dialectic criticism, through the methodology of the three levels of narrative interpretation. Thus, we will reach the political unconscious of Canadian society figured in the novel. As a result, we hope to contribute to the study of gender and the study of 20th century North American Literature.